Crossing Boundaries - Solomon, Mildred Z. (The Hastings Center report, 2019)
I met Dan Callahan in 1986—when I came to pitch him. Coming from a sleek office setting near Boston, I was intrigued by The Hastings Center's higgledy-piggledy environment where so many smart people got to work in a relaxed, inviting atmosphere. I had noticed that the Center was producing a great deal of policy work on a wide range of topics but didn't seem to go further than publishing the highly valuable guidance developed under Dan Callahan's leadership. I ended my pitch, “Look, Dan, where Hastings gets bored and wants to go on to the next topic, my group in Boston gets interested.” To my great pleasure, and despite his skepticism, Dan accepted the pitch. Beyond his generous responsiveness to unproven young people, Dan had many other virtues. For one, he was a boundary crosser.